The jesuit funds in the libraries of Rome. a contribution to your knowledge - Miguel Alonso, Aurora (Revista General de Información y Documentación, 2018)
In Papal Rome, the centers of the Society of Jesus were accumulating since its foundation (1540) an enormous bibliographic and documentary wealth. The complex history lived by the Jesuits for more than three centuries was reflected in their librarian collections, until the annexation of the Papal States, in 1876, to the new unified Italy when they were mostly incorporated into the newly created National Library of Rome, as one of its main founding collections. In this work it is collected the history and operation of the libraries that were formed in the main centers of Rome, Roman College, Professed House, Novitiate and Germanic- Hungarian College, divided into three periods: the first, growth phase, since the inauguration from the Roman College until the dissolution of the Society of Jesus in 1773, the second phase of disintegration and regroupment, from 1773 until the restoration of the Society of Jesus, 1815, and the third, from 1815 until the inauguration of the National Library of Rome in 1876. Throughout the work, in addition, we refer to authors, collections and Spanish libraries.
Keywords: Jesuit libraries; Roman College; Professed House (Rome); Novitiate (Rome); Germanic- Hungarian College (Rome).